Pemberian Aromaterapi Lemon dan Peppermint Terhadap Penurunan Intensitas Mual dan Muntah Ibu Hamil - Rochkmana, Meika Jaya; Hapsari, Endah Titi; Boediarsih, Boediarsih (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Nausea followed by vomiting is a condition that is often found in pregnant women in the first trimester. This condition will appear 6 weeks after menstruation and normally disappear after entering the 10th week of pregnancy. The cases of nausea followed by vomiting in the first pregnancy are about 60%-80% and about 40%-60% in the second pregnancy. Cases of nausea and vomiting in Demak Regency in 2019 were 85% and in 2020 it had increased to 90%. This research determined the effectiveness of lemon and peppermint aromatherapy on the intensity of nausea and vomiting in pregnant women. This study is a quasi-experiment research with a two group pretest posttest design. The population consisted of 59 pregnant women, with a sample of 36 pregnant women who met the inclusion criteria using the purposive sampling technique. Group 1 treated with lemon aromatherapy consisted of 18 people and Group 2 treated with peppermint aromatherapy consisted of 18 people. Pregnancy-Unique Quantification of Emesis and Nausea scale (PUQE) was used to measure the Nausea scale. Statistical test using the Mann-Whitney test. The research found that lemon aromatherapy is more effective than peppermint aromatherapy in the intensity of nausea and vomiting in pregnant women with the significant result p-value 0.001. This research suggests that pregnant women should be able to deal with nausea and vomiting independently by giving lemon aromatherapy.